Inclusão educacional e o Plano Institucional de Desenvolvimento e Expansão (PIDE) da Universidade Federal de Uberlândia (UFU) : interfaces de um processo político e educacional - Freitas, Marcia Guimarães de (2016)
The aim of the present study was to analyze how inclusion is proposed and implemented by Universidade Federal de Uberlândia (UFU). We tried to identify the concept of inclusion fomented in the Developing and Expanding Institutional Plans (PIDEs) and if the goals and actions listed in the documents contribute to minimize physical and attitudinal barriers faced by disabled students in the institutional area. Based on Foucault‟s studies, we understand the theme “inclusion” as a strategy, or a power device, aiming to introduce everybody into the economic game; making that each one becomes responsible for providing their needs and learning. We found a possible way of articulating this notion of inclusion with studies related to management and strategic planning at universities, mentioning as a research source the National System used to evaluate Graduate Courses (SINAES) and specifically the Developing Institutional Plan. Although they are two fields with distinct theoretical approaches, the articulations were possible, because through the methodological tools, we managed to glimpse that several active devices can take effects in the institution routine. The inclusion devices and the ones from PDI are strongly crossed by the business and educational speeches; and articulated to reach goals committed with the neoliberal society, where universities are constituted and which they constitute in an immanence relation. We found that inclusion, under the effects of the historical process, becomes, nowadays, a state imperative and gets to universities, given that, according to the neoliberal vision, education becomes a condition so that people can operate with the inclusion logic in all their actions. We also found that, at UFU, this inclusive imperative can be seen in the documents (PIDEs) in two ways: through the social inclusion and the accessibility as a policy of students‟ insertion and permanence.